Getting rid of the shackles from the support: construction of recoverable semi-homogeneous catalysts with attapulgite. Issue 29 (13th July 2021) - Guo, Ruixiang; Wang, Gang; Liu, Wei; Yao, Zibei; Liu, Weisheng
Abstract : Using a strategy of "adsorption–desorption–adsorption" to immobilize homogeneous catalysts, these active species, which can be dispersed at the molecular scale, could catalyze the reaction herein like a homogeneous catalyst. Abstract : Traditionally, immobilized catalysts sacrifice part of their catalytic activity for their recyclability. To reproduce the catalytic activity of these active species, we construct a novel strategy called "adsorption–desorption–adsorption". Since the active material and the support of the catalyst are connected by an electrostatic force, the catalyst can release the active material into the solvent during the heating process of the reaction to achieve the effect of homogeneous catalysis. When the reaction is over and the temperature is lowered, the catalyst reabsorbs again to achieve the effect of heterogeneous catalysis. Through this "adsorption–desorption–adsorption" catalytic process, the catalyst can become a new semi-homogeneous catalyst, and this strategy could be extended to other immobilized catalysts.